THE AVAILABILITY OF INDONESIAN COAL TO MEET THE 2050 DEMAND - Gandhi Kurnia Hudaya; Nendaryono Madiutomo (Puslitbang tekMIRA, 2019)
Coal is the important energy source for industry and power plant in Indonesia. Its reserve is quite abundant around 28.5 billion tons. The Government of Indonesia issued the National Energy Policy (NEP) to target 25% of coal use of the national energy mix in 2050. The NEP directs the national energy management for the provision and utilization of primary energy. However, there are worries about the ability of coal reserve in accommodating the demand from domestic and export needs. The National Energy Council recommended coal production restriction policy for anticipation measures. This research investigated the current state of the coal reserves and the government policy to meet the target in 2050 using Vensim program. In the Vensim, a model was built to represent a coal supply-demand system. Several scenarios were simulated to analyze the relationship between the government policy and the coal reserve. The result shows that government intervention such as coal production restriction policy is needed to ensure Indonesia’s coal reserve can fulfill domestic demand for power generation and industry by 2050.